Wellness Tourism Experience on the Rise Post COVID: Behavioural Demand Trends and Expectations - Hekmat, Nasim (2022)
This chapter synthesizes the emergence of the growing wellness tourism segment in an era of post-COVID-19 travel when consumer mentality has been radically changed and shifted towards different needs. This includes any activity that allows tourists to work on themselves mentally or physically and present several considerations and recommendations for the wellness industry to take full advantage of tourism opportunities moving forward. It aims to help understand consumer behaviour and preferences by predicting wellness tourism trends and developments, acknowledging the gaps in the research available for understanding wellness tourism post covid and reflecting the experience economy perspective in the sector. A research method was developed, including a literature review and survey application to potential wellness tourists. Discussion of results is provided, along with main conclusions, allowing the identification of trends and development measures to help improve wellness tourism in a post-COVID era.